Enhancing sustainability in concrete construction: A comprehensive review of plastic waste as an aggregate material - Hamada H.M.; Al-Attar A.; Abed F.; Beddu S.; Humada A.M.; Majdi A.; Yousif S.T.; Thomas B.S. (Elsevier B.V., 2025)
With the proliferation of the population and the evolution of lifestyles, the issue of plastic waste has emerged as a significant environmental challenge due to its non-biodegradable nature and voluminous generation. However, there has been a scarcity of substantial research efforts to examine the influence of plastic waste on the properties of concrete. The current study aims to undertake a comprehensive review of the findings from previous research endeavors, with a specific focus on the period between 2020 and 2024, to investigate the potential of utilizing plastic waste as an aggregate in cement concrete components. To present a comprehensive review of this study, the literature pertaining to the use of plastic waste as aggregates in cement concrete has been examined and analyzed. The key types of plastic waste and their recycling as aggregates in concrete mixtures are briefly discussed. The physical and mechanical properties of these plastics and their impact on the mechanical and durability properties of concrete were evaluated, as well as their economic benefits and the limitations to their usage. The results indicate that the addition of specific categories of plastic waste enhances the workability and reduces the density, compressive, flexural, and tensile strengths of concrete to acceptable levels compared to the control samples. The incorporation of plastic waste into the cement concrete matrix leads to significant economic benefits by reducing the consumption of raw materials and the emission of CO2 into the atmosphere. The addition of plastic waste as an aggregate in concrete mixtures can also decrease the thermal conductivity property of concrete. Furthermore, the durability properties can be improved with the incorporation of a small quantity of plastic waste. Additionally, the use of plastic waste as an aggregate in concrete mixtures has the potential to reduce production costs and alleviate environmental pollution for a cleaner environment. Therefore, this investigation concludes that the appropriate utilization of plastic waste in construction projects can greatly enhance sustainability and mitigate the adverse impact of plastic waste on the environment. ? 2023